EFFECTIVE WAYS TO TEACH A CHILD ENGLISH AS A SECOND LANGUAGE: EFFECTIVE WAYS TO TEACH A CHILD ENGLISH AS A SECOND LANGUAGE - Almatova, Umida (Журнал иностранных языков и лингвистики, 2021)
This article provides information on effective ways to teach English.